2024
DOI: 10.3390/antiox13030292
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Antioxidant and Antimicrobial Activities in Bee-Collected Pollen through Solid-State Fermentation: A Comparative Analysis of Bioactive Compounds

Adriana Cristina Urcan,
Adriana Dalila Criste,
Daniel Severus Dezmirean
et al.

Abstract: The present study investigates the impact of solid-state fermentation on bee-collected pollen using a consortium of Lactobacillus plantarum, Apilactobacillus kunkeei, and Lactobacillus acidophilus. Another aim is to compare the nutritional and bioactive properties of natural versus fermented pollen, focusing on macronutrient composition, pH, acidity, lactic acid content, and profiles of polyphenolics and flavonoids. Our results indicated significant enhancements in the contents of amino acids, suggesting impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Pasteurized BCP showed significantly lower antimicrobial and antioxidant activities after fermentation than unprocessed fermented BCP, indicating that BCP natural microbiota further contributes to antimicrobial and antioxidant properties exerted by artificially fermented BCP [ 21 ]. Urcan et al showed that it is feasible to enhance the antioxidant and antimicrobial activity of BCP through solid-state fermentation [ 53 ]. Similarly, a recent study reported that microbiota enhanced BB antiviral activity against Influenza A virus, as shown by the higher antiviral potential of artificially fermented BCP compared to fresh unfermented BCP [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pasteurized BCP showed significantly lower antimicrobial and antioxidant activities after fermentation than unprocessed fermented BCP, indicating that BCP natural microbiota further contributes to antimicrobial and antioxidant properties exerted by artificially fermented BCP [ 21 ]. Urcan et al showed that it is feasible to enhance the antioxidant and antimicrobial activity of BCP through solid-state fermentation [ 53 ]. Similarly, a recent study reported that microbiota enhanced BB antiviral activity against Influenza A virus, as shown by the higher antiviral potential of artificially fermented BCP compared to fresh unfermented BCP [ 23 ].…”
Section: Discussionmentioning
confidence: 99%